Business modeling and software design : 10th International Symposium, BMSD 2020, Berlin, Germany, July 6-8, 2020, Proceedings /: 10th International Symposium, BMSD 2020, Berlin, Germany, July 6-8, 2020, Proceedings. (2020) - Unknown
No abstract available